Same-Sex Marriage Across Cultures: Contrasting Perspectives Between Proponent and Opponent Countries - Sidiqah, Meliyani (Legal Standing : Jurnal Ilmu Hukum, 2025)
This study examines the intricate social dynamics surrounding the legalization and rejection of same-sex marriage across various countries, particularly through the interplay of moral and ethical values, social norms, and formal state laws. Methodologically, this study adopts normative juridical research and relies on secondary sources of data, including primary, secondary, and tertiary legal materials. A comparative method is employed to contrast and contextualize diverse legal and socio-political perspectives. The data, collected through extensive library research, are analysed using a qualitative analytical framework. This study identifies two central points of focus. First, the factors that distinguish the perspectives of proponent and opponent countries regarding same-sex marriage. Second, the variables influencing the strengthening or weakening of support for same-sex marriage within different national and cultural contexts. Generally, proponent countries emphasize adherence to universal human rights instruments, including the recognition of same-sex marriage, while opponent countries often rely on contextual interpretations shaped by cultural and religious values. The findings of this study reveal five key factors that account for the differing perspectives on same-sex marriage: the enduring debate between universality versus relativity of human rights, differing ideological orientations, contrasting conceptions of the relationship between state and religion, varied constructions of moral benchmarks upheld by states, and the distinctive national legal frameworks adopted. In addition, five further determinants are identified as shaping the intensity of public and legal support: prevailing societal values (individualistic or communal), judicial decisions, the presence of civil society movements, the influence of public figures, and the broader national objectives pursued.